The Effect of Oxytocin Massage on Breast Milk Production and Self-Efficacy During the Postpartum - Finta Isti Kundarti (KHD Production, 2025)
Oxytocin massage is a complementary intervention designed to enhance breast milk production and support breastfeeding success during the postpartum period. Insufficient milk supply and low maternal confidence are frequently reported barriers to achieving exclusive breastfeeding. This study aimed to determine the effect of oxytocin massage on breast milk production and self-efficacy among postpartum mothers. A quasi-experimental design with a non-equivalent control group was used. The study involved 52 participants, who were divided into an intervention group and a control group, each consisting of 26 participants, on the third day after delivery. Data were collected using an oxytocin massage checklist, a measuring cup to assess milk production, and a self-efficacy questionnaire. The Wilcoxon test with a significance level of α = 0.05 was employed for data analysis. The results indicated a significant difference in breast milk production between the intervention group and the control group, with a p-value of 0.000. A significant difference in self-efficacy was also observed, with the intervention group scoring higher than the control group, as indicated by a p-value of 0.001. These findings demonstrate that oxytocin massage effectively increases both breast milk production and maternal self-efficacy in breastfeeding. Beyond physiological benefits through oxytocin release, the intervention also enhances psychological readiness, making oxytocin massage a recommended supportive therapy for postpartum breastfeeding success.